Akibat Hukum Terhadap Perjanjian Waralaba Tanpa Melakukan Pendaftaran Prospektus Waralaba - Imansah, Rifai; Hakim, Luqman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
A franchise agreement or franchise is a legal subject action between the giver and recipient of the franchise which has legal consequences, namely reciprocal obligations and rights between the two parties. The agreement can be said to be valid if it fulfills the elements of the requirements for a franchise agreement as regulated in the Civil Code Article 1320 which explains that the validity of an agreement is agreement, competence, a certain thing, a lawful cause. The principle of freedom of contract in a franchise agreement is not absolute. Because there are certain restrictions regulated in statutory regulations have difference to the flight hours, (3) decision-making variables that not have a difference to the flight hours.